MANFAAT DAUN JAMBU BIJI (PSIDIUM GUAJAVA) UNTUK KESEHATAN - Antok Nurwidi Antara (STIKES Wira Husada Yogyakarta, 2019)
Background: Guava fruit (Psidium guajava) or Guava is one of the fruits that can grow in tropical and subtropical climates, such as in Mexico, South America, Indonesia and neighboring countries 3. Citizens in some countries use Guava leaves. as traditional or folk medicine.Objective: This study aims to provide an explanation of the benefits of guava leaves for health based on the literature study (literature review) obtained by researchers in a certain period of time.Method: This literature review examines 8 research articles or journals related to guava leaves. Articles or journals used are taken from the data base, namely: doaj.org in 2015 until April 2019.Results: Guava leaves have beneficial effects on animal health, including: Has anti-inflammatory power, Increases attention to the effects of blood thinning, As an antioxidant or anti-diabetes, As for human health, among others, Helps overcome diarrhea, Inhibits dental caries, Has a significant influence on changes in Hb and platelet levels in young women, Has cytotoxic activity against T47D5 cellsConclusion: The leaves of herbal medicine seeds provide several important benefits for animal health and some important benefits also for human health.